2017
DOI: 10.9734/bjmmr/2017/33545
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Undergraduate Students’ Perception of the Educational Environment of a Medical School in Zambia Provided a Framework for Strategic Planning

Abstract: Aim: To propose a strategy for improvement of undergraduate students' learning environment based on analysis of their perceptions. Methods: Medical, Pharmacy, and Physiotherapy undergraduate students participated in the study. The study used a quantitative descriptive design, based on the Dundee Ready Educational Environment Measure (DREEM) inventory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…9 Measurements of learning environments have been utilized in different ways including comparing different training sites, different curricular models, and to guide strategic planning. 10 At the time of this study, the University of Zambia has an undergraduate medical and pharmacy education program in the School of Medicine. The study therefore examined undergraduate students' perceptions of the learning environments in the 2 programmes with the aim of understanding factors that enable or hinder teaching and learning and identifying any differences in the 2 learning contexts.…”
Section: Introductionmentioning
confidence: 99%
“…9 Measurements of learning environments have been utilized in different ways including comparing different training sites, different curricular models, and to guide strategic planning. 10 At the time of this study, the University of Zambia has an undergraduate medical and pharmacy education program in the School of Medicine. The study therefore examined undergraduate students' perceptions of the learning environments in the 2 programmes with the aim of understanding factors that enable or hinder teaching and learning and identifying any differences in the 2 learning contexts.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature reflects that only a few pharmacy institutes have previously been evaluated for their educational environment through the DREEM scale. There is only one report from Pakistan on the educational environment of a public-sector university providing pharmacy education and a few reports from other countries (Brown et al, 2011;Ezeala & Moleki, 2017;Ezeala & Moleki, 2018), whereas, the educational environment of the private-sector academic institutes in Pakistan has not been evaluated before. The students' rating of the private pharmacy institutes for the total DREEM score, as determined in this study, was found to be similar to a previous report from a public-sector university of Pakistan, thereby, suggesting that the students of private-sector pharmacy institutes/universities of Islamabad and Rawalpindi are equally satisfied with their educational environment.…”
Section: Discussionmentioning
confidence: 99%
“…DREEM was introduced in the late 1990s by a panel of 30 health professional educators and then validated through testing on students in several countries (Roff et al, 1997;Miles et al, 2012). The tool was originally designed for the assessment of the educational environment in medical and other health professions institutes but has also been employed and validated with little modifications for institutes offering pharmacy and other allied health professions and nonmedical education (Brown et al, 2011;Atapattu et al, 2015;Ezeala & Moleki, 2017;Ezeala & Moleki, 2018;Memon et al, 2018). The DREEM questionnaire constituting of 50 items, to be answered on a five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%